(untitled) (Research, Society and Development, 2021)
Rural Education is a teaching modality, conquered by social movements, aimed at meeting the specific needs of people living in rural areas. The objective of the research was to analyze how teachers and students at a rural school assess the influences and implications after the implementation of the Agricultural Sciences discipline in the school curriculum. For data collection, surveys were carried out in the second half of 2019, with 20 students and 4 teachers from the Town School Procópio Faria, in Vila Rica/MT. To collect data, questionnaires consisting of 6 open questions were used, whose data were analyzed by the technique of Content Analysis. The results indicate that the discipline should continue, that, through it, students started to value both the man and the work that is carried out by these individuals in the field. Many students stated that they learned to eat more nutritious foods through the course and that they started to analyze the origin of the food, whether it was organic or not. As for the professors, in addition to defending the permanence of the discipline, they also highlighted the need to add more specific components and that it should be taught by a specialized professor or with experience in the area. Therefore, it is concluded that the implementation of specific curricular components in schools located in rural areas contributed to the appreciation of rural people and that more studies on the subject are needed, due to the lack of bibliography and relevance to the field of knowledge.